Primate taxonomy: Species and conservation. Issue 1 (2nd January 2014) - Rylands, Anthony B.; Mittermeier, Russell A.
<x xml:space="preserve">Abstract</x> Primatology as a discrete branch of science involving the study of primate behavior and ecology took off in the 1960s after discovery of the importance of primates as models for biomedical research and the realization that primates provide insights into the evolutionary history of humans. Osman Hill's unfortunately incomplete monograph series on the comparative anatomy and taxonomy of the primates1 and the Napiers' 1967 A Handbook of Living Primates2 recorded the world's view of primate diversity at this time. This taxonomy remained the baseline for nearly three decades, with the diversity of each genus being represented by some species, but extensively as subspecies.